Peningkatan Keterampilan Membaca Pemahaman Tingkat Terampil Melalui Metode SQ3R Pada Mahasiswa Semester VII STBA JIA - Hoftman, Rainhard Oliver (Universitas Negeri Semarang, 2019)
Dokkai or reading understanding in Japanese is one of the lessons that combines several skills such as kanji, sentence pattern, translation, and culture. From all those several skills dokkai is a lesson that need accuracy. The obstacles in learning dokkai as the error understanding and error translation is a problem that must be overcome. This research is using the method of SQ3R, that are survey, question, read, recite, and review. These stages can describes reading or discourse into several part that can be easily understood. This research is the action research that using two cycle, each cycle consists of 2 meetings. The object of the research is the students of the 7thsemester that took Jyoukyuu Dokkai as the lesson. The result of the research from the action that using this method is the skills of the students in understanding discourse become increase, finish is study and the activities become better than before. The student has the new method in understanding new reading and discourse.